EVALUASI PENERAPAN SISTEM AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA PT. CIPUTRA INTERNASIONAL CABANG MANADO - Katili, Indra Ningsih; Morasa, Jenny; Budiarso, Novi S. (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Every organization requires an information system to facilitate the activities that have been planned and supervised to control the financial cash flow of the company, The purpose of this study was to know how the accounting information system of cash receipts in the department of PT. Ciputra International Manado branch, by tracking network accounting procedures that make up the system of cash receipts. The method used descriptive analysis method which research began by collecting and filtering the entire incoming information thoroughly and detail later elaborated in order to obtain a clear picture. The results showed that the accounting information system of cash receipts at the hospital department of PT. Ciputra International Manado branch is adequate because they were appropriate and meets the essential elements of an accounting information system that is human resources, equipment, forms or documents, records, procedures and reports. cash receipts and disbursements procedures have been arranged and done his best to avoid distortions that might occur, so that to date accounting information system cash receipts and disbursements in the department of PT. Ciputra International Manado branch can be done effectively. The solution is management, should implement every part to running the task as the authority.Keywords: accounting information systems, cash receipts